2021
DOI: 10.52095/gp.2021.8113
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of body dysmorphic disorder in the community: a systematic review

Abstract: Objective: Body dysmorphic disorder (BDD) is an underdiagnosed condition among the general population with significant associated morbidity and mortality. Symptoms of BDD include worrying excessively about a particular part of the body, repeatedly checking oneself in the mirror and attempting to cover up particular areas of the body. Aim:To determine the prevalence of BDD within the global population. To perform a further subgroup analysis to identify groups that have a higher prevalence than the general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
15
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 92 publications
3
15
5
Order By: Relevance
“…Research shows that BDD is often an underdiagnosed condition in the general population. 40 This could also be true within the elite sport population. To address this issue, BDD should be a topic in a clinical setting with elite athletes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Research shows that BDD is often an underdiagnosed condition in the general population. 40 This could also be true within the elite sport population. To address this issue, BDD should be a topic in a clinical setting with elite athletes.…”
Section: Discussionmentioning
confidence: 98%
“…Another interesting result is that 15 of the 20 athletes diagnosed with OCD and OCD-related disorders were diagnosed with BDD. Research shows that BDD is often an underdiagnosed condition in the general population 40. This could also be true within the elite sport population.…”
Section: Discussionmentioning
confidence: 99%
“…BDD prevalence is estimated to be between 0.5 and 3.2 [18,29]. However, these estimates include only studies from Europe and the U.S., as population-level epidemiological studies have not been conducted in other cultures [29].…”
Section: Culture Comparisonmentioning
confidence: 99%
“…BDD prevalence is estimated to be between 0.5 and 3.2 [18,29]. However, these estimates include only studies from Europe and the U.S., as population-level epidemiological studies have not been conducted in other cultures [29]. Three representative studies from Germany (N = 2129, N = 2552 and N = 2510) found prevalence rates ranging from 1.7-2.9% in adults [9,30,31].…”
Section: Culture Comparisonmentioning
confidence: 99%
“…Eating disorders (Wu et al, 2020) and body dysmorphic disorder (Minty & Minty, 2021) are worldwide public health concerns. Both anorexia nervosa and body dysmorphic disorder relate to distortions in the perception of self-appearance .…”
mentioning
confidence: 99%